Ex‐Dividend Profitability and Institutional Trading Skill - HENRY, TYLER R.; KOSKI, JENNIFER L. (Journal of Finance, 2017)
ABSTRACT We use institutional trading data to examine whether skilled institutions exploit positive abnormal ex‐dividend returns. Results show that institutions concentrate trading around certain ex‐dates, and earn higher profits around these events. Dividend capture trades represent 6% of all institutional buy trades but contribute 15% of overall abnormal returns. Institutional dividend capture trading is persistent. Institutional ex‐day profitability is also strongly cross‐sectionally related to trade execution skill. The relation between execution skill and profits disappears around placebo non‐ex‐days. Results suggest that skilled institutions target certain opportunities rather than benefiting uniformly over time. Furthermore, only skilled institutions can profit from dividend capture.